IMPLEMENTATION OF INDONESIAN POLICE (POLRI) TASK IN CHANGING ERA: A PARADIGMATIC STUDY ON THE MODEL OF COMMUNITY PERPOLISM (POLMAS), LEGAL ENFORCEMENT AND LOCAL FUNCTION - Rudy Cahya Kurniawan (Jurnal Pembaharuan Hukum, 2019)
Before Society Police was carried out the community still complained about the police's performance which was not maximal in overcoming and minimizing the security of criminal acts within the community itself, so it was hoped that with the establishment of Society Police, Society Police could help the police in dealing with crime around the community so safe and orderly environment. The writing of this dissertation is essentially focused on the implementation of Polri's duties in the changing era with a paradigmatic analysis of the model of Society Police (Polmas), law enforcement and local wisdom. This effort requires cooperation between law enforcement officials. The thing that needs to be understood from the Polmas model above is the pattern of the legal system towards the implementation of Indonesian Police duties related to Society Police and problems relating to the community, especially related to solving small problems such as security and order in the community through Society Police and influencing factors the implementation of Society Police in creating a conducive society security situation . The theory or concept of criminal policy is used as the analytical system.